Nós propomos! Pato Branco com o ensino da geografia do lugar - Rozin, Eliane Maria (2019)
The dissertation present was developed with students support and participation in Group of Research, Representations, Spaces, Times and Languages in Educational Experiences (RETLEE), in research line Culture, educative process and teacher formation. Accomplished in partnership with the State University of the Paraná West, Campus of Francisco Beltrão, Parana (UNIOESTE/FB), and Institute of Geography and Spatial Planning of Lisbon University (IGOT-UL/PT) to the implementation of We Proposed Project! Citizenship and Innovation in Geography Education. This research objectified analyzed the Geographic teaching and learning processes, through the case study, while research methodology, by means of the place study. The research was accomplished with 33 students of the first Year High School, with Geography teacher support, in State School Teacher Agostinho Pereira, in Pato Branco/PR city. The purpose was evaluate the possibility investigate to best teaching and learning Geography. Also comprise who occurs the sense appropriation in local context, fomenting the students participation in problems identification and in proposals search to changes. The research development follows some indicative stages of the We Proposed Project! And covered actions as: 01) choice the school and the research subjects; 02) proposal presentation to school direction and Cooperation Agreement signature; 03) diagnosis; 04) presentation We Proposed Project! to students; 05) works groups with the themes selection, the logotype creation, objectives and schedule; 06) Master Plan study and municipal map; 07) field work; 08) proposal elaboration to the problematic listed by groups; 09) forum socialization with the proposals intervention presentation in I Geography Teaching Colloquium with meaning in Research We Proposed! 10) projects socialization with the I Seminary We Proposed! Pato Branco. The problematic chosen was: Information plate at bus stops; Transit and Bike Paths; Feed and water for street pets; SOS Life Pets and Citizen Literature. This research work presents relevant results to the geography education that have a personal sense, in social meaning of the students relationship with the world, so brought the change wish and the commitment with the students emancipation. To admit the real conflicts started the relationship object and researcher, both interconnected in knowledge construction. Their being and live were valuate from the research, the approach with the place problems and the solutions proposals give sense to scientific content. The personal consciousness and social formation was constructed from the material and sociocultural, in relationship with the place. To teacher, the project established objectives, defined action and elected instruments, also the cause rupture with the Geography teach way, by world thoughts and reality.